ENHANCING THE VALIDITY AND FAIRNESS OF LAWYER LICENSING: EMPIRICAL EVIDENCE SUPPORTING INNOVATIVE PATHWAYS - Deborah Merritt; Eileen Kaufman; Andrea Anne Curcio (Washington University Journal of Law and Policy, 2024)
A two-day written bar exam cannot test a prospective lawyer’s ability to counsel clients, investigate facts, research novel issues, negotiate with adversaries, or perform other essential tasks. The conventional exam has also become a test of resources, favoring candidates who can afford to buy commercial prep courses and devote 8-10 weeks to full-time study. Cognizant of these flaws, several states have adopted—or begun exploring—other approaches to licensing. Oregon has already implemented a small program that allows some law graduates to demonstrate their competence by practicing under the supervision of a licensed attorney and compiling portfolios of work product from that supervised practice. Candidates submit those portfolios, which include materials related to client counseling and negotiation, to bar examiners for independent assessment. Starting in May 2024, the Oregon program will be available to more graduates. Other states are exploring similar approaches.
Keywords: Bar Exam; Compotency; Licensing